Profitable Dividend Yield Investment Strategy: Empirical Evidence from Indonesian Stock Exchange - Achmad, Aditya; Wijayani, Dahyang Ika Leni; Misra, Isra (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2026)
Purpose: This study seeks to address the challenges of the dividend trap phenomenon and irrational investor behavior amid extreme stock price fluctuations. Stock price volatility often triggers irrational investor behavior and asymmetric information, rendering traditional index-based investing insufficient for risk mitigation. Methodology/approach: A quantitative approach was used in analyzing the data. Portfolios were formed through quintile classification based on two main variables: Gross Profitability to Assets (GPA) and Dividend Yield (DY). Portfolio performance was then evaluated using risk-adjusted return (Sharpe Ratio) and geometric mean return metrics to compare the performance of the PDY strategy against the benchmark Jakarta Composite Index (JCI) and fixed-income assets. Findings: The results show that the best quintile portfolio (G5D5) consistently provides superior returns compared to the market and fixed-income assets. This finding provides empirical confirmation of the application of signaling theory and bird-in-the-hand theory in emerging markets, where dividend payments accompanied by strong profitability serve as credible signals of a company's prospects. Practical Implication: This study provides guidance for investors and investment managers in developing a defensive portfolio strategy that is still able to provide capital appreciation and stable dividend income, especially in an inefficient market. Originality: The novelty of the study lies in the integration of gross profitability and dividend yield criteria with a specific focus on the Islamic stock index (ISSI), an area that is still rarely explored in depth in the asset pricing literature in Indonesia.